Distance et proximité - François Cardi (La Nouvelle Revue du Travail)
For many years, Sébastien Calvet was a Socialist Party supporter, before moving on in 2012 to follow François Hollande's election campaign for Libération, a French daily. Working as a political photo journalist goes well beyond taking pictures, however. combining periods of uncertainty with phases of negotiation and moments of improvisation. Calvet would need to demonstrate photographic talent along with a sense of power relationships and responsive intuition. In the end, his work involved social practice as much as the art of photography, with anticipation becoming as important as information and editorial logic often overriding any photographic intention.